The Economics behind the Epidemic: Afghan Opium Price and Prescription Opioids in the US - Claudio Deiana; Ludovica Giua; Roberto Nistico (Institute of Labor Economics (IZA), 2019)
We investigate the effect of variations in the price of opium in Afghanistan on per capita dispensation of prescription opioids in the US. Quarterly county-level data for 2003-2016 indicate that reductions in opium prices significantly increase the quantity of opioids prescribed. The increase involves natural and semi-synthetic but not fully synthetics opioids, therefore suggesting that the effect is moderated by the amount of opium contained in the products. While this evidence could suggest a pass-through of lower production costs to retail prices, boosting patients' demand for opioids, we fail to detect significant effects of changes in retail prices on per capita dispensation. Moreover, firm-level analysis reveals that advertising expenses of opioid producers increase following opium price declines and so do their stock prices and profits. Overall, our findings suggest that supply-side economic incentives might have played an important role in the opioid epidemic.
Keywords: I11; I12; I18; L65; 330; prescription opioids; drugs; opium price; supply-side economic incentives